Thermal aspects of STELA (sustainable thermally enhanced LNAPL attenuation) - Akhbari, Daria, author; Sale, Tom, advisor; Bau, Domenico, committee member; Ronayne, Michael, committee member (Colorado State University. Libraries, 2013)
Extensive bodies of light non-aqueous phase liquids (LNAPLs) are commonly found beneath petroleum facilities. Related concerns include lateral spreading of LNAPL, impacts to groundwater, and impacts to indoor air. Recent studies have shown that natural losses of LNAPL can be on the order of thousands of gallons per acre per year and temperature is a primary factor controlling rates of natural losses. Results of the laboratory and field experiments suggest that LNAPL impacted media in the range of 18-300C can have loss rates that are an order of magnitude greater than media at temperatures less than 18ºC. The vision that has emerged from recent work is that passive thermal management strategies could enhance natural losses of LNAPL and significantly reduce the longevity of LNAPL. Owing to this new understanding, plans were developed for a small-scale field demonstration of sustainable thermally enhanced LNAPL attenuation (STELA) at a former refinery in Wyoming, located adjacent to the North Platte River. The overarching objective of the STELA initiative is to develop a new technology for LNAPLs that is more effective, faster, more sustainable, and/or lower cost than current options. The primary objective of the field demonstration is to collect data needed to evaluate cost and performance at field sites. In November 2011, seventeen multilevel sampling systems were installed in a 10m by 10m area. Preheating temperature and water quality data were collected through the multilevel samplers over a period of 10 months. In August 2012, ten heating elements, including submersible heat trace wires wrapped around 7.6 cm ID PVC pipe with thermostat controls, were installed upgradient of the sampling network to deliver heat to sustain subsurface temperature in an LNAPL body. The heating elements were energized in September 2012. Subsequently, effects of the heating elements on the subsurface temperature were monitored using 17 multilevel sampling systems equipped with 6 thermocouples for 10 months. Preheating data indicates that in the absence of heating, subsurface temperatures are in the range of 18-30°C for 40 days per year. Data collected from September 2012 to July 2013 indicates that with heating, conditions can be maintained in the target range for 60 to 200 days per year depending upon proximity to the heat source. A principle challenge is heat loss to the surface in the winter. Minimum and maximum power inputs have been 15 kw-hr/day and 30 kw-hr/day occurring, respectively in October and May. Assuming an energy cost of 0.10 kw-hr, this equates to costs of 1.5 $/day to 3 $/day. An independent experiment using Geo-net layer showed that using Gas Permeable Insulation/Heat Sink (GPIHS) system has the potential to enhance the ability of the heating system to sustain temperature beneath the ground surface, and, potentially decrease the power costs. A primary challenge with evaluation and design of STELA systems is anticipating the appropriate spacing of heating elements and necessary energy inputs. Herein this challenge is met by developing a model, calibrated to field data, which can be used to design a full-scale STELA remedies. The overarching objective of the modeling is to demonstrate methods that can be employ to evaluate and/or design full-scale STELA systems. At 5m downgradient of the heating elements, the developed model, accurately, predicted 60 days of the effective season in 2012. Also, the simulation results anticipate that by keeping the heating system activated for three years, the effective season will increase each year. At 5m downgradient of the heating elements, model results suggested 120 days and 150 days of effective season for 2013 and 2014, respectively as compared to 60 days in the first year. The ability of the model to anticipate the effective season for the next years makes the model a useful tool to design and evaluate the future STELA systems. Calibration of the model to the field data shows that exothermic reactions associated with LNAPL losses can change the heat distribution at the system. In addition, the simulation results indicate that the losses at the subsurface are in the range of 5,000 to 10,000gal/acre/yr. These anticipated loss rates are consistent with the previous values reported by McCoy (2012) in 2012 (~900-11,000gal/acre/yr.) A conceptual STELA design is developed in the last chapter to explore the cost of a STELA system at a 1-hectare site. The design is based on condition at the former refinery in Wyoming where the STELA field demonstration was conducted. The cost analysis study indicated that the primary cost is the heating elements installation. The second significant cost is the operation costs, and the third significant cost that can be reduced is the energy source. The cost estimates normalized to common units indicated that the total cost ranges between $590,000 to $720,000 per hectare, $11.9 to $14.4 per cubic meter of treated soil, and $1.3 to $1.5 liter of LNAPL removed depends on the energy source, heating system and the degradation rate. Cost of this magnitude support the hypothesis that STELA has the potential to have cost that is lower than other options employed for LNAPL remediation.
Keywords: groundwater; heat transport; LNAPL; MT3DMS; natural attenuation; remediation